A Flexible and Biomimetic Olfactory Synapse with Gasotransmitter‐Mediated Plasticity. (22nd February 2023) - Deng, Yuping; Zhao, Mingyou; Ma, Yuan; Liu, Shangbin; Liu, Mingda; Shen, Boyu; Li, Rongfeng; Ding, He; Cheng, Huanyu; Sheng, Xing; Fu, Wangyang; Li, Zehui; et al.
Abstract: Neuromorphic electronics has demonstrated great promise in mimicking the sensory and memory functions of biological systems. However, synaptic devices with desirable sensitivity, selectivity, and operational voltage imitating the olfactory system have rarely been reported. Here, a flexible and biomimetic olfactory synapse based on an organic electrochemical transistor (OECT) coupled with a breath‐figure derived porous solid polymer electrolyte (SPE) is proposed. The device demonstrates excellent sensitivity with a ppb‐level response limit and desirable selectivity toward hydrogen sulfide (H2 S) over other gases, and successfully achieves wireless real‐time detection of excessive concentration of H2 S from rotten eggs. H2 S‐mediated synaptic plasticity is accomplished with the device and typical synaptic behaviors are realized, including short‐term memory (STM), long‐term memory (LTM), transition from STM to LTM, etc., enabling the imitation of potential cumulative damages upon H2 S exposure. The proposed device paves new ways toward next‐generation olfactory systems capable of sensing and memorizing functionalities mimicking neurobiological systems, offering critical materials strategies to accomplish intelligent artificial sensory systems. Abstract : A flexible and biomimetic olfactory synapse is developed based on organic electrochemical transistors coupled with breath‐figure derived porous solid polymer electrolytes. The device demonstrates a ppb‐level response limit and desirable selectivity toward hydrogen sulfide (H2 S). H2 S‐mediated synaptic plasticity is accomplished and typical synaptic behaviors are realized, including short‐term memory (STM), long‐term memory (LTM), and transition from STM to LTM.